Sulfated glucan can improve the immune efficacy of Newcastle disease vaccine in chicken - Wang, Mi; Yang, Ruile; Zhang, Lifang; Meng, Xinyu; Fei, Chenzhong; Zhang, Keyu; Wang, Xiaoyang; Zheng, Wenli; Xiao, Sui; Zhang, Saiqi; Xue, Feiqun; Hu, Yuanliang (International journal of biological macromolecules, 2014)
To evaluate the immune effect of sulfated glucan from saccharomyces cerevisiae (SGSC) on chickens, two experiments were researched. In vitro experiment, the effects of SGSC on chicken splenic lymphocyte proliferation were determined. The results displayed that SGSC could significantly stimulate chicken splenic lymphocyte proliferation. In vivo experiment, 200 14-day-old chickens were averagely divided into 5 groups. The chickens, except blank control (BC) group, were vaccinated with Newcastle disease (ND) vaccine, repeated vaccination at 28 days old. At the same time of the first vaccination, the chickens in three SGSC groups were injected, respectively, with the SGSC at low, medium and high concentrations, in vaccination control (VC) and BC group, with equal volume of physiological saline, once a day for three successive days. On days 7, 14, 21, 28, 35 and 42 after the first vaccination, the lymphocyte proliferation, serum antibody titer and interleukin-2 (IL-2) and interferon-gamma (IFN-γ) were measured. The results showed that SGSC at suitable dose could significantly promote lymphocyte proliferation, enhance serum antibody titer, and improve serum IL-2 and IFN-γ concentrations. It indicated that SGSC could significantly improve the immune efficacy of Newcastle disease vaccine, and would be as the candidate of a new-type immune adjuvant.